Experimental study of the effects of continuous rod hold-down anchorages on the cyclic response of wood frame shear walls. (1st March 2021) - Estrella, Xavier; Malek, Sardar; Almazán, José Luis; Guindos, Pablo; Santa María, Hernán
Highlights: Experimental investigation of wood frame walls with continuous rod hold-downs. The nail spacing has a relevant influence on the properties of wood frame walls. Remarkable stiffness degradation was observed under large lateral displacements. Design standards inaccurately predict the mechanical properties of wood frame walls. Abstract: When designing mid-rise wood frame buildings in high seismicity areas, overturning moments induce large tensile forces in the anchoring system that cannot be resisted by conventional discrete hold-downs. To address this issue, continuous rod hold-downs are used instead to transfer the generated tensile loads to the foundation. However, investigations on the lateral response of wood frame walls employing this anchorage system are quite limited. This paper presents an experimental–numerical study aimed at providing a better understanding of the response of such walls under lateral loads. Four specimens with different configurations were tested under lateral cyclic load, and their behavior was compared with that of walls with discrete hold-downs. Results showed that employing the continuous rod system increases the wall strength by 35.8%, with the specimens behaving elastically up to drifts of about 0.8%. The walls exhibited a marked stiffness degradation during the tests, keeping a residual value of about 15–20% of the initial stiffness. Further analyses showed that the Special Design Provisions for Wind and Seismic (SDPWS) guidelines underestimate the wall strengths by 39.9% and overestimate the stiffnesses by 37.5%, on average. Finally, a nonlinear model was developed to investigate the specimens of this research in depth, showing a special failure pattern that concentrates the damage in the nails located at the central studs of the wall.